Deterministic Extensional Viscosity and Cracking Index of Polypropylene-Modified-Asphalt Binder - Abdul-Rahim Ibrahim Al-Hadidy; Zeena Ahmed Al-Kazzaz; Ahmed A. Mohammed Ali (Tikrit Journal of Engineering Sciences, 2020)
The extensional viscosity and cracking prospectus of polypropylene modified asphalt cement (PPMAC) was explored. Forty/fifty penetration class asphalt cement with five-contents of polypropylene polymer were chosen. Conventional traits such as: Standard penetration, standard softening point, ductility, utter viscosity, elasticity moduli, penetration prospectus, ageing, cracking prospectus, homogeneity, and extensional viscosity were performed on PPMAC. The PPMAC shows better viscosity, elasticity, enduringness and lower cracking properties at cold regions.